Bioinformatics analysis of γD-crystallin protein P23T mutation in a congenital cataract family - DONG Qi; ZHENG Shu; XU Wei-zhen; CAI Shan-rong; YAO Ke (浙江大学学报. 农业与生命科学版)
A Pro-23→Thr (P23T) substitution in γD-crystallin protein was identified in a hereditary congenital cataract family through previous study. The amino acid sequence, protein domain and motifs, and three-dimension structure of γD-crystallin protein and its mutant were analyzed and predicted. The results showed that the mutation of γD-crystallin protein could affect the ability of the protein to bind itself with calcium ions, thereby inducing dynamic unbalance of the calcium ions in lens. The inter-molecular hydrogen-bonds were rearranged, which would reduce the solubility of mutant γD protein. Protein modeling suggests that the effect of this mutation is a subtle one which affect the local polarity of the crystallin molecule surface, and may affect the manner of interaction between γD-crystallin protein and other proteins.